New therapeutic options in the treatment of odontomas - Bálint Trimmel; Zoltán Nagy; Szabolcs Gyulai-Gaál (Hungarian Dental Association, 2021)
Odontoma is a benign, odontogenic tumour composed of mixed epithelial and mesenchymal tissues. Based on the literature recurrence is rare after complete extirpation. In our case, we present a two-stage surgical treatment approach for a recurrent complex odontoma, which was first operated two years earlier. The twenty-year-old patient presented an abscess localized to the area of the right mandibular angle. The radiological images, revealed an area filled with an odontoma- like lesion and the impacted lower wisdom tooth. Due to the risk of jaw fracture and alveolar nerve injury, a twostage surgical procedure was applied from intraoral access. During the first surgery, the odontoma was removed and the bony defect was marsupialized. Four months later, the right lower wisdom tooth and the epithelial lining of the bony defect were removed. The second surgery was performed without alveolar nerve injury, the bony defect was filled with platelet-rich fibrin and primarily wound-closure was applied. Healing was uneventful. During three month healing time the original anatomical conditions were reconstructed in the previous surgical area.